Comparative Analysis of Fatigue Energy Characteristics of S355J2 Steel Subjected to Multi-Axis Loads - Cyprian T. Lachowicz (Materials, 2020)
In this study, a novel test system for estimating bending and torsion fatigue under selectable kinematic and dynamic loading modes was constructed. Using S355J2 steel specimens, a series of tests were conducted to determine material sensitivity to different load paths and loading modes. The experimental results were supplemented with the results of numerical analyses, on the basis of which the components of strain and stress tensors for subsequent analyses were determined in the entire working part of the specimen. An original method for determining specific strain energy components was used. The experimental results showed the grouping of data according to the mode of loading chosen. This could signify that the selected fatigue models are sensitive to certain loading scenarios. We performed in- depth data analysis and complex numerical simulations, formulating likely explanations for the observed effect